Faktor Pending Klaim BPJS Di Rumah Sakit Umum Daerah Provinsi NTB - Rizka Maisaroh, Anika; Lalu Sulaiman; Sismulyanto (Jurnal Kesehatan Qamarul Huda, 2024)
Pending claims at the Health Social Security Administering Agency (BPJS) are a serious problem that can disrupt the smooth process of health services in hospitals. This study aims to analyze the factors that cause delays in BPJS claims in hospitals. The research method used was primary and secondary data analysis, involving data collection from medical records, interviews with hospital staff, and analysis of BPJS claims data. The research results show that several factors are the main causes of delays in BPJS claims at hospitals. These factors include administrative problems, such as errors in filling out claim forms and completeness of documents; technical problems in the hospital's computerized system which is not aligned with the BPJS system; as well as external factors such as complex policies and regulations. The implication of these findings is the need for corrective action in the hospital administration system and alignment with the BPJS system. Improving information and communications technology infrastructure is also important to minimize technical obstacles. Apart from that, collaboration between hospitals and BPJS in formulating more efficient and transparent policies is also needed to address this problem holistically. This research contributes to further understanding of the factors that influence delays in BPJS claims in hospitals, as well as providing a basis for developing more effective solutions in improving the efficiency and quality of health services in Indonesia.